Factors affecting the emergence of Korean tutorial agencies in Iloilo City - Nuevaorlanda, Jeremae; Paredes, Leah; Peñascosa, Sheralyn; Solatorio, Kathy Marie
A research was conducted to determine the factors that affect the proliferation of Korean Tutorial Schools in iloilo City. The respondents of the study is composed of forty (40) Korean students, twenty (20 tutors), and four (4) operators coming from 4 different agencies or schools in the city. A different questionnaire was given to each set of respondents. An interview was also conducted for the tutors to get the information needed. Based on the tally sheet, percentages, frequency, and other statistical tools were used to generate the relevant results and relationships between the variables. Based on the findings, there are three main factors that affect the proliferation of Korean Tutorial Agencies in the city and these are the proficiency of tutors, increasing number of Koreans, and income. The increasing number of Koreans coming to the Philippines is due to lenient immigration policy and its strategic location. Koreans choose to study particularly in Iloilo City due to the low cost of living compared to other metropolitan areas. Also, tutors who are proficient in speaking English and are willing to teach Korean students have increased in number for the past couple of years. This factor has significantly contributed to the continuing emergence of tutorial agencies.. Income generate by tutors and operators at the same time is an important consideration in the putting up a tutorial school. The respondents reveal that adequate compensation and return of investment is guaranteed in offering tutorial services.